JOINT ECONOMIC LOT SIZING ; IMPERFECT PRODUCTION PROCESS ; SUPPLIER ; MANUFACTURER ; TOTAL EXPECTED COST - SUCI YUNIAR (NIM : 23415039), SRI
This study aims to develop a joint economic lot size model between a supplier and a manufacturer for imperfect production processes with probabilistic demand and constant lead time. The supplier produces the product within a certain time interval then sent to the manufacturer with a lot size quantity. The imperfect production process of suppliers is characterized by probability defect product (γ). Decision variables for this model are order sizeÃ‚Â’s manufacturer, production lot sizeÃ‚Â’s supplier, safety stockÃ‚Â’s manufacturer and reorder point levels manufacturer. The optimal decision variable is obtained by minimizing the total expected cost for the supplier and the manufacturer. The optimal solution is obtained by developing algorithm that modifies the Hadley and Within algorithm (1963) and Hsu (2013). The model compared with transactional partnership model. In the transactional partnership model, the supplier does not participate in the efficiency of the inventory system so that the lot size production of the supplier's production equals lot size order of the manufacturer's. A numerical example is given as an illustration of the JELS model and the transactional partnership model. Results of numerical examples then made a comparison of model. The comparison of model is better than the transactional partnership model as it results in a more minimal total cost of Rp. 90,921,759,7 / Year with total order of 16,492,605 Units and service level of manufacturer is 99,969%. The sensitivity analysis of the model is carried out by changing the parameters appropriate for the model model of behavior developed. The parameters that most affect the order lot size are the cost parameters of the supplier's store cost, the manufacturer's save rate, and the rate of demand.